Sodium‐Ion Batteries: A Nanosheet Array of Cu2Se Intercalation Compound with Expanded Interlayer Space for Sodium Ion Storage (Adv. Energy Mater. 25/2020). Issue 25 (7th July 2020) - Xiao, Yuanhua; Zhao, Xiaobing; Wang, Xuezhao; Su, Dangcheng; Bai, Shuo; Chen, Wei; Fang, Shaoming; Zhou, Liming; Cheng, Hui‐Ming; Li, Feng
Abstract : In article number 2000666, Xuezhao Wang, Shaoming Fang, Feng Li and co‐workers report the development of a nanosheet array of Cu2 Se‐CTAB (cetyltrimethyl ammonium bromide) intercalation compound with expanded interlayer space that is directly grown on Cu foil at room temperature. When used as anode for sodium‐ion batteries, the CTAB inserts into the interlayer space, buffering the volume expansion, confining the fast growth of Cu metal particles and restricting the shuttling of polyselenide.